The Effect of the Intensity of Telework Use on Employees’ Work-Life Balance - Grincevičienė, Neringa (Buhalterinės apskaitos teorija ir praktika, 2020)
The intensive penetration of information and communication technologies into the labour market has also determined the modernisation of work organization processes. The digitization of information and telecommunications enabled to perform most of intellectual activities not only in the work premises but also in other spaces distant from the main workplace. Thus, as the technology revolution gradually releases modern intellectual work from the constraints of the physical location, telework is becoming an increasingly accelerating trend in the world. Together with technological changes allowing to reach the employee 24 hours a day and 7 days a week create challenges for teleworkers seeking to successfully reconcile two areas of life – work and personal life. Employees from different fields, among them accounting, audit, finances, analysis and others that carry out tasks via telework face this challenge. Relevance of the scientific research problem formulated in this paper was determined by the lack of studies in the scientific research to date, which would evaluate the intensity of telework use as an important factor that has a different effect on work-life balance. The research aim is to reveal the effect of the intensity of telework use on employee work-life balance. A quantitative study – the survey of telework employees was conducted and 320 respondents were surveyed. The results of the empirical study revealed that the intensity of telework use had equally positive effect only on two dimensions of work-life balance: time intended for the family and friends and time intended for oneself.